Rhinitis Alergi: Etiologi, Patofisiologi, Diagnosis dan Tatalaksana - Indah Kurnia Putri Waruwu; Isabela Irene Pangestu; Syalwa Meutia; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Allergic rhinitis is an inflammatory disease that is triggered by the occurrence of allergic reactions in patients with atopy who have previously been sensitized to the same allergen and the release of a chemical mediator when there is repeated exposure to that specific allergen which causes an inflammatory reaction in the patient. Rhinitis which is triggered by an allergic reaction to an allergen is one of the cases of nasal inflammation found in all human races. The incidence of rhinitis is more common, especially in children with male gender. The incidence of rhinitis that occurs in children will decrease with increasing age of these children. In adulthood, the incidence of rhinitis can be said to decrease and is rarely found. Even though allergic rhinitis has a course of disease, clinical manifestations that are not too dangerous for the patient's condition, this disease can still experience recurrences if the triggering allergen is not removed. This recurrence cannot be allowed to continue to occur because over time it will become a chronic symptom which can trigger various complications and also decrease the quality of life of sufferers. Adequate management and avoidance of triggering allergens are the main steps to avoid recurrence of allergic rhinitis.